Pathogenic Fungal Infection in the Lung - Zhi Li; Zhi Li; Gen Lu; Guangxun Meng (Frontiers in Immunology, 2019)
Respiratory fungal infection is a severe clinical problem, especially in patients with compromised immune functions. Aspergillus, Cryptococcus, Pneumocystis, and endemic fungi are major pulmonary fungal pathogens that are able to result in life-threatening invasive diseases. Growing data being reported have indicated that multiple cells and molecules orchestrate the host's response to a fungal infection in the lung. Upon fungal challenge, innate myeloid cells including macrophages, dendritic cells (DC), and recruited neutrophils establish the first line of defense through the phagocytosis and secretion of cytokines. Natural killer cells control the fungal expansion in the lung via the direct and indirect killing of invading organisms. Adaptive immune cells including Th1 and Th17 cells confer anti-fungal activity by producing their signature cytokines, interferon-γ, and IL-17. In addition, lung epithelial cells (LEC) also participate in the resistance against fungal infection by internalization, inflammatory cytokine production, or antimicrobial peptide secretion. In the host cells mentioned above, various molecules with distinct functions modulate the immune defense signaling: Pattern recognition receptors (PRRs) such as dectin-1 expressed on the cell surface are involved in fungal recognition; adaptor proteins such as MyD88 and TRAF6 are required for transduction of signals to the nucleus for transcriptional regulation; inflammasomes also play crucial roles in the host's defense against a fungal infection in the lung. Furthermore, transcriptional factors modulate the transcriptions of a series of genes, especially those encoding cytokines and chemokines, which are predominant regulators in the infectious microenvironment, mediating the cellular and molecular immune responses against a fungal infection in the lung.